Authenticity and instagrammable sceneries : a content analysis of DMO’s perceptions of social media relevance in Porto de Galinhas (Brazil) - ALMEIDA, Bruna Tavares de (2023)
The way people travel has been changing, especially due to technology. The internet and social media platforms have been inserted in the daily life of billions of people, and Instagram can be considered one of the most influential current networks. However, the authenticity of what has been called instagrammable sceneries has been questioned, even though authenticity’s importance to tourists’ satisfaction is already known by tourism scholars. The current study set the primary goal of analyzing in which way city and state governments take authenticity into consideration when creating and promoting instagrammable sceneries in Porto de Galinhas, Pernambuco, Brazil. For this goal to be achieved it was necessary to identify instagrammable sceneries; to present tourist instagrammable sceneries in Porto de Galinhas; and to describe how the city and state governments perceive instagrammable sceneries. It was also required to describe how the city and state governments use authenticity to create and promote instagrammable sceneries in Porto de Galinhas. To be able to complete such objectives, a qualitative approach was used, with bibliographic and documentary research, observation, and interviews. These interviews were conducted with representatives from the city and state Tourism Authorities, and they were analyzed through a content analysis. Several instagrammable sceneries were identified, as were the concepts of instagrammable, scenery and authenticity by Ipojuca and Pernambuco’s representatives. Authenticity is seen as a spontaneously emerging culture, while instagrammable is related to the promotion of an experience, and sceneries are considered as simple city signs. The working relationship between the municipality and its governing state was found to be extremely fragile, especially for tourism. Besides, no evidence of the use of authenticity in the construction of instagrammable sceneries by the State was found, as little investment is made towards research and construction of such sceneries.